DESKRIPSI PELAKSANAAN PENGKAJIAN KEPERAWATAN HOLISTIK DI IGD RSUD ULIN BANJARMASIN - Sadiq, Khairus; Wahid, Abdurahman; Hafifah, Ifa (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
The nursing process including nursing assessment has constraints in it’s application includingwithin the complex scope of IGD with high workload. The nursing philosophy views theindividual in a holistic way as a whole, which had biological, psychological, social, cultural andspiritual dimensions. Objective To determine the description of holistic implementation nursingassessment by nurses at IGD RSUD Ulin Banjarmasin. This study used Descriptive research on34 nurses in IGD room of Ulin Banjarmasin General Hospital taken in total sampling. The studywas conducted on 20-27 November 2017. Result of research got description of nursing holisticstudy showed result of biological aspect of applikative category 76%, psychological aspect ofapplikative category 91%, social aspect of applikative category 76%, spiritual aspect categorynot applicative 59% and culture aspect applicative and non applicative category with percentageof 50%. Nurses as health professionals provide health services, especially comprehensive nursingcare. It was suggested that nurses need to improve their ability to support the implementation ofholistic nursing assessment especially on the spiritual aspect.